2017
DOI: 10.22514/sv133.062017.14
|View full text |Cite
|
Sign up to set email alerts
|

Can first trimester placental biomarkers copeptin and PP13 predict preeclampsia in advanced age nulliparous women?

Abstract: Preeclampsia (PE) affects approximately 3% of all pregnancies and it is still a major cause of adverse perinatal outcome. PE is a multisystem pregnancy related disorder of unknown aetiology with a progressive course and with no established therapy. In recent times excessive research was conducted on early screening for PE with an aim to reduce the prevalence of the disease with early medical treatment starting from the first trimester of pregnancy in the high-risk group. The aim of this study is to detect if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Another study suggested an increased maternal serum copeptin levels in pregnant women with IUGR as compared with pregnant women with AGA fetuses. So, our study supports the previous studies that maternal serum copeptin levels are raised in pregnant women with IUGR as compared to pregnant women with adequate for gestational age fetuses which can be helpful in detection of IUGR [22].…”
Section: R E S U L T Ssupporting
confidence: 91%
“…Another study suggested an increased maternal serum copeptin levels in pregnant women with IUGR as compared with pregnant women with AGA fetuses. So, our study supports the previous studies that maternal serum copeptin levels are raised in pregnant women with IUGR as compared to pregnant women with adequate for gestational age fetuses which can be helpful in detection of IUGR [22].…”
Section: R E S U L T Ssupporting
confidence: 91%
“…Measurement of PP13 is not a routine investigation in clinical medicine but gained much attention in pregnancyrelated research. In many studies, quantification of PP13 in biological sample was done either by ELISA [19][20][21][22][66][67][68][69][70][71][72][73][74][75][76] or by dissociation-enhanced lanthanide fluorescence immunoassay (DELFIA) methods. [77][78][79][80][81][82][83][84][85][86] The underlying principle of ELISA for the estimation of PP13 is an enzyme-linked antibody sandwich method.…”
Section: Quantification Of Pp13mentioning
confidence: 99%
“…Beljan et al 22 conducted a prospective study to detect whether the first trimester serum PP13 and copeptin can predict preeclampsia in advanced age nulliparous women. This study confirmed a significant contribution for the combination of two biomarkers for the prediction of preeclampsia ( p = 0.007).…”
Section: Screening Performancementioning
confidence: 99%
See 1 more Smart Citation